May Measurement Month 2017–2019: A Community-Wide Opportunistic Blood Pressure Screening Campaign in Hong Kong - Joyce Tik Sze Li; Amy Shuk Man Lam; Brian Tomlinson; Vivian Wing Yan Lee (International Journal of Hypertension)
Introduction. Hypertension is a modifiable risk factor for multiple cardiovascular diseases. Early identification and intervention of new cases are crucial to improve patients’ outcomes. May Measurement Month (MMM) is an annual global synchronised blood pressure (BP) screening campaign. Participants can have their BP measured at the screening sites. It may be a possible way to identify undiagnosed hypertensive patients in the population. Methods. It was a cross-sectional study of BP among Hong Kong adults. Multiple screening sites were set in local community pharmacies and on the campus of the Chinese University of Hong Kong. Participants were asked to fill in a questionnaire regarding their demographics, medical history, and social history. Then, they took at least one BP reading using an automated sphygmomanometer after sitting at for 5 minutes. Up to three BP readings were taken and recorded for each participant, with one-minute intervals between readings. Results. A total of 3224 adults participated in MMM between 2017 and 2019. The average BP among the 3224 participants was 139.8/75.5 mmHg. The prevalence of hypertension was 2282 (70.8%), of which 635 (27.8%) were undiagnosed before MMM. Among the 1647 participants previously diagnosed with hypertension, 1007 (61.1%) had uncontrolled hypertension. Conclusion. A high number of cases can be identified with untreated, or treated but uncontrolled, hypertension from MMM. Citizens should be encouraged to check BP regularly and take follow-up actions if hypertension is suspected.